Thimerosal and vaccines: ¿austims and neurological disorders? - Hernández Díaz, Herminio R. (2007)
It has been possible to prevent many diseases thanks to the advance of the medical sciences and the development of effective vaccines. Millions of deaths have been avoided, and the mortality and morbidity of vaccine-preventable diseases have been drastically reduced, in the populations where vaccine campaigns are carried out. Vaccines, nevertheless, can present undesirable effects or events related to their application, which despite their rarity have been grossly exaggerated. Lately there are attempts to imply thimerosal, a vaccine preservant, as the possible cause of autism, attributing to it a neurotoxic effect. The present evidences of many different kinds do not support a neurotoxic role for thimerosal. The statements on thimerosal neurotoxicity are not supported by evidence; the studies show no association between vaccines containing thimerosal and disorders of the autistic spectrum. The conclusion is that there is no causal effect between a type of vaccines or whether they contain thimerosal and the development of a neurological disorder of the autistic spectrum.